Do we have "the theory" for a socialist transformation? Cuba 2023 - P. García Brigos , Jesus (2023)
In this paper brief reflections are presented regarding the development of the relations between the real practices of socialist transformation up to the present and the theoretical elaborations about this process, insisting on essential specificities of this social revolution, first of all regarding the order of the transformations and the centrality of the necessary transcendence of the adversarial private property system that has been the axis of the development of societies since the processes of decomposition of the original communities up to capitalism. A brief characterization of the current picture of the process of transformations in Cuba, the essential challenges and the proposal of five theses to be considered for the sustainable progress of the Cuban socialist transformation in the current conditions are hereby presented.